GROVé, K Inventory of documents - GROVé, K (ARCA, 2018)
Reminiscences of the Anglo Boer War, native question, clippings
COVERAGE 1924-1954; 15 files; 0.20 metre
Keywords: GROVé, K; DF Malan; Native Problem